2017
DOI: 10.3390/catal7080228
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Propylene Oxide to 3-Hydroxy Butyric Acid Using a Cobalt Carbonyl Ionic Liquid Catalyst

Abstract: Abstract:The reported catalytic system demonstrates the possibility of efficient mass production of 3-hydroxybutyric acid (3-HBA) from inexpensive raw materials. The direct coupling of propylene oxide, water, and CO was catalyzed by 1-butyl-3-methylimidazolium cobalt tetracarbonyl ([Bmim][Co(CO) 4 ]) ionic liquid to form 3-HBA with >99% conversion (49% selectivity) under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Ring-expansion carbonylation is the most widely studied topic of epoxide transformation because it utilizes carbon monoxide as a C1 resource to produce chemically important critical intermediate β-lactones in an atom economic way. , The produced β-lactones have inherent ring strain, which makes them a highly sought target for producing industrially important value-added chemicals like poly­(β-hydroxyalkanotes) a biodegradable polymer, , β-hydroxy acids, succinic acid, succinic anhydrides, acrylic acid, etc. , Despite the growing need for β-lactones, their commercial production is still a challenging task . In this regard, ring-expansion carbonylation of epoxides is an attractive direct one-pot method for the production of β-lactones from the commercially available epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…Ring-expansion carbonylation is the most widely studied topic of epoxide transformation because it utilizes carbon monoxide as a C1 resource to produce chemically important critical intermediate β-lactones in an atom economic way. , The produced β-lactones have inherent ring strain, which makes them a highly sought target for producing industrially important value-added chemicals like poly­(β-hydroxyalkanotes) a biodegradable polymer, , β-hydroxy acids, succinic acid, succinic anhydrides, acrylic acid, etc. , Despite the growing need for β-lactones, their commercial production is still a challenging task . In this regard, ring-expansion carbonylation of epoxides is an attractive direct one-pot method for the production of β-lactones from the commercially available epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…β-Lactones are a class of strained 4-membered heterocycles with widespread importance in the chemical industry owing to their application as critical intermediates in the production of compounds such as poly­(β-hydroxyalkanoates), which are important biodegradable polyesters, β-hydroxy acids, , succinic anhydrides, and acrylic acids. , In recent years, ring-expansion carbonylation of epoxides has emerged as a convenient, direct, and atomically economic method for the production of β-lactones. Furthermore, this synthetic strategy allows the value-added utilization of the inexpensive C1 resource CO and epoxides, both of which can be commercially produced by a variety of practical methods and are thus readily available. , The [Co­(CO) 4 ] − catalyzed ring-expansion carbonylation of epoxides to lactones has been known for several decades. Furthermore, Coates et al reported a series of well-defined homogeneous bimetallic Lewis acid–base pair catalysts, i.e., ([Lewis acid] + [Co­(CO) 4 ] − ), for the ring-expansion carbonylation of epoxides and proposed the catalytic mechanism shown in Scheme . The mechanism involves (i) epoxide activation by a Lewis-acidic metal ion; (ii) ring opening by a Lewis-basic Co­(CO) 4 – ion; (iii) CO insertion into a Co-alkyl bond; and (iv) ring closure to generate the lactone . Among the ([Lewis acid] + [Co­(CO) 4 ] − )-type systems, porphyrin-based catalytic systems have proved to be the most efficient to date, even though they have limitations in terms of tedious product separation and catalyst recycling, both of which are critical for commercial-scale applicability. , …”
Section: Introductionmentioning
confidence: 99%
“…The efficient transformation of epoxide into β-lactone has attracted considerable attention owing to its synthetic significance in the production of acrylic acid, β-hydroxyacids, β-hydroxyester, succinic anhydride, , and biodegradable poly­(β-hydroxy­butyrate). Realizing the industrial importance of β-lactones, a number of homogeneous catalysts have been reported for the conversion of epoxide into a lactone. Among them, Coates et al established that the well-defined homogeneous bimetallic complex tetraphenylporphyrin chromium tetracarbonyl cobaltate [TPPCr]­[Co­(CO) 4 ] exhibited excellent conversion of epoxides to lactones, which is the best catalyst to date for epoxide carbonylation. Moreover, these bimetallic complexes demonstrated the necessity of active ion pair for efficient carbonylation and gave important mechanistic insights (Scheme ).…”
Section: Introductionmentioning
confidence: 99%